THE EFFECTIVENESS OF PEER FEEDBACK ON WRITING NARRATIVE TEXT - Maya Oktavia Nirmala (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
Abstact: This study intends to investigate the effectiveness of peer feedback technique to improve students writing skill in writing narrative text. The study was conducted on April 2018 at MTsN 1 Batu. It employed experimental design involving two different classes of second grade they were also divided into experimental and control group. The experimental group was treated by peer feedback while the control group was treated by teacher feedback. The data ware gather through pretest and posttest. The pretest held to know the score before treatment were given. Meanwhile, the posttest were held to know significant effect after treatment using peer feedback The data was analyzed by using t-test The result of the data showed that were a significant difference score in writing narrative text between students who were taught by using peer feedback and without taught using it. It can be seen in the result of hypothesis testing through t-test. The significant value 0.001 in this less than the significance level of 0.05 (0.000<0.05), which means that the data of this study were considered to have significant difference. Therefore, the hypothesis of this study were accepted. It means that peer feedback technique significantly improve student writing skill in English teaching and learning process at MTsN 1 Batu. Key words: effectiveness, peer feedback, writing narrative text